The Concept of Developing Islamic Education Teaching Materials Based on Scientific Integration - Zulkifli, Zulkifli; Zurqoni, Zurqoni; Khojir, Khojir (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This research aims to formulate a conceptual framework for the development of Islamic education teaching materials based on scientific integration in the context of non-formal Islamic education (majelis taklim). The research uses a qualitative approach through literature studies as the main data source, complemented by limited non-participatory observations as contextual supporting data. The data were analyzed descriptive-analytically through thematic categorization and conceptual synthesis. Literature synthesis shows that scientific integration has implications for strengthening conceptual understanding as well as opportunities for developing students' reflective and critical thinking skills. The research output is in the form of integrative teaching material design principles which include relevance, comprehensiveness, integrability, contextuality, and applicability. Integration is positioned as a reconstruction of the relationship between revelation, reason, and reality that enriches the understanding of Islam and strengthens the internalization of Islamic values in modern life. This conceptual framework is expected to be a reference for educators and curriculum developers in designing contextual and integrative Islamic education teaching materials.